Functional and RNA-Sequencing Analysis Revealed Expression of a Novel Stay-Green Gene from Zoysia japonica (ZjSGR) Caused Chlorophyll Degradation and Accelerated Senescence in Arabidopsis - Teng, Ke; Chang, Zhihui; Li, Xiao; Sun, Xinbo; Liang, Xiaohong; Xu, Lixin; Chao, Yuehui; Han, Liebao (Frontiers in Plant Science, 2016)
Senescence is not only an important developmental process, but also a responsive regulation to abiotic and biotic stress for plants. Stay-green protein plays crucial roles in plant senescence and chlorophyll degradation. However, the underlying mechanisms were not well studied, particularly in non-model plants. In this study, a novel stay-green gene, ZjSGR, was isolated from Zoysia japonica. Subcellular localization result demonstrated that ZjSGR was localized in the chloroplasts. Quantitative real-time PCR results together with promoter activity determination using transgenic Arabidopsis confirmed that ZjSGR could be induced by darkness, ABA and MeJA. Its expression levels could also be up-regulated by natural senescence, but suppressed by SA treatments. Overexpression of ZjSGR in Arabidopsis resulted in a rapid yellowing phenotype; complementary experiments proved that ZjSGR was a functional homologue of AtNYE1 from Arabidopsis thaliana. Overexpression of ZjSGR accelerated chlorophyll degradation and impaired photosynthesis in Arabidopsis. Transmission electron microscopy observation revealed that overexpression of ZjSGR decomposed the chloroplasts structure. RNA sequencing analysis showed that ZjSGR could play multiple roles in senescence and chlorophyll degradation by regulating hormone signal transduction and the expression of a large number of senescence and environmental stress related genes. Our study provides a better understanding of the roles of SGRs, and new insight into the senescence and chlorophyll degradation mechanisms in plants.